2016
DOI: 10.1016/j.ijpharm.2016.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Hot-melt extruded filaments based on pharmaceutical grade polymers for 3D printing by fused deposition modeling

Abstract: Fused deposition modeling (FDM) is a 3D printing technique based on the deposition of successive layers of thermoplastic materials following their softening/melting. Such a technique holds huge potential for the manufacturing of pharmaceutical products and is currently under extensive investigation. Challenges in this field are mainly related to the paucity of adequate filaments composed of pharmaceutical grade materials, which are needed for feeding the FDM equipment. Accordingly, a number of polymers of comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
216
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(221 citation statements)
references
References 36 publications
1
216
0
4
Order By: Relevance
“…Several pharmaceutical grade polymers, including HPC, were recently investigated to obtain drug loaded filaments via HME 15, 17, 21 . A capsular device printed by FDM using HPC filament was explored for pulsatile drug release 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pharmaceutical grade polymers, including HPC, were recently investigated to obtain drug loaded filaments via HME 15, 17, 21 . A capsular device printed by FDM using HPC filament was explored for pulsatile drug release 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the different developed 3D printing technologies, fused deposition modeling (FDM) has several significant advantages such as low-cost manufacturing, the compatibility of using the combination of pharmaceutical grade polymers with APIs through hot-melt extrusion (HME) and the ability to fabricate hollow objects 1416 . Previous pharmaceutical researchers attempted to use FDM-based 3D printing mainly in fabricating drug delivery systems with immediate or controlled release characteristics 1719 , hot-melt extruding filaments of pharmaceutical grade polymers 15, 20, 21 , lowering printing temperatures 22 , and preparing personalized topical drug delivery together with 3D scanning 23 . To our knowledge, there is no report on the FDM based hollow tablets for intragastric floating sustained release (FSR) of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2. It has been observed that the 3D printing extrusion temperature is generally higher than that needed for filament extrusion [34], due to the material's short residence time in the liquefier's reservoir and the limited power of the feeding system's stepper motor (NEMA 17), compared to the single-screw extruder. Also, the liquefier temperature set on CAM program reflects the temperature of the melt reservoir on the upper part of the nozzle, close to the print head's temperature sensor.…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…However, today, it is almost impossible to count the sale of FDM systems as after the collapse of the technology's patent, which earlier held by Stratasys Inc, various firms started the production of cost effective printers. Technically, FDM follows extrusion principle as discussed in plethora of publications . Further, the key elements of FDM and process parameters are highlighted by others.…”
Section: Dp Technologies For Pmc Systemsmentioning
confidence: 99%